Predictors of teenage pregnancy in Ethiopia: a multilevel analysis - Betelhem Eshetu Birhanu; Deresse Legesse Kebede; Alemayehu Bayray Kahsay; Abate Bekele Belachew (BMC, 2019)
Abstract Background In Ethiopia, pregnancy, and childbearing begin at an early age. Teenage pregnancy has long-term implications for girls, their families, and communities. However, multilevel predictors of teenage pregnancy are not well studied yet. Several studies are focused only on the effects of individual-level characteristics but ignored the community level effect. This, in turn, could result in biased estimation of predictors of teenage pregnancy. Therefore, this study aimed to identify the individual and community level factors that determine teenage pregnancy in Ethiopia. Method The data were extracted from the 2016 Ethiopian Demographic and Health Survey. The study included a sample from 645 clusters of 2679 (weighted) women aged 20-24 years. The data were collected using a two-stage cluster design that includes selection of enumeration areas as a first stage and selection of households as a second stage. A two-level mixed-effect logistic regression model was fitted to determine the individual and community level factors associated with teenage pregnancy. Result The study revealed that 2134(79.6%) of women aged 20-24 years experienced pregnancy during their adolescent stage. Being sexually active before age 15[AOR = 7.9; 95%CI: 4.5, 13.8]; being married before age 15[AOR = 30; 9%CI: 16.7, 53.9] and being a rural dweller [AOR = 2.2; 95%CI: 1.4, 3.6] were positively associated with teenage pregnancy. A woman living in a community with a lower proportion of contraceptive users [AOR = 2.3; 95%CI: 1.5, 3.5]; had also a statistically significant association with teenage pregnancy. Conclusions and recommendation Various factors at both the individual and community level determined teenage pregnancy. Therefore, the government should work on the prevention of early marriage, early sexual initiation and on improving the utilization of family planning in the community to protect them from pregnancy that occur at early age.